El método Singapur y el pensamiento lógico – matemático en niños de preparatoria de la Escuela de Educación Básica Dr. Edison Calle Loaiza de la ciudad de Loja, periodo 2023-2024. - Armijos Labanda, Daniela Cecibel (2024)
The ability to reason logically and solve problems efficiently is characterized by logical-mathematical thinking, which enables children to enhance fundamental skills for cognitive and personal development. Thus, this study examined how the Singapore method strengthens logical-mathematical reasoning in high school students at the Escuela de Educación Básica Dr. Edison Calle Loaiza of La Paz. Edison Calle Loaiza of the city of Loja, period 2023-2024; for this, a mixed approach was used, which made it possible to perform a quantitative analysis to tabulate the data collected from the application of the instrument and qualitative to interpret these data; the study was conducted under a descriptive scope so that accurate details of the detected phenomena could be provided, and inductive - deductive methods were used to analyze the phenomenon studied and to draw conclusions, as well as the analytical - synthetic approach which allowed for better comprehension of the information. Likewise, the Evamat-0 instrument was used to determine the level of development of the logical-mathematical thinking of the high school children, showing that 70.83% of the children were located in the low zone, 12.5% in the medium zone and 16.67% in the high zone. Consequently, a guide of activities based on the Singapore method has been developed, which aims to improve the children's logical-mathematical abilities. By utilizing concrete strategies and resources based on practical and meaningful experiences, the structure of the program stimulates students' desire and will to acquire new knowledge. Key words: concrete material, Singapore method, mathematical skills.